HUMERAL SHAFT FRACTURE FIXATION WITH ANTEGRADE INTRAMEDULLARY INTERLOCKING NAIL: A STUDY - DR.RAJU KULKARNI,; DR. SREE KRISHNA PATURI, (International Journal of Pharma and Bio Sciences, 2015)
Operative management of Humeral shaft Fractures can be with Plate osteosynthesis or with Intra medullary nailing. As the intra medullary nails can be introduced in a closed manner, they preserve the fracture hematoma, providing early fracture consolidation with higher union rates and low infection rates. Interlocking achieves rotational stability, providing early mobilization of the neighboring joints. But with antegrade nailing they do have a disadvantage of causing shoulder stiffness. In this study, we have tried to analyze the outcome in terms of time for consolidation, union rates, functional results & complication of humeral shaft fractures managed with Antegrade intramedullary interlocking. Methods: 25 Adult patients with acute humeral shaft fractures were treated with closed intramedullary nailing in an antegrade manner. 20 males & 5Females with an average age of 37.5Yrs (25-70Yrs). All the patients were followed over a period of 2 years and the results were analyzed. Results: 23 (92%) Fractures united with an average consolidation time of 13.5 weeks (10-16Weeks), 1 (4%) fracture ended in nonunion. There were 2 (8%) cases of intraoperative fracture comminution which did not affect fracture healing. There was 1 (4%) case of transient iatrogenic radial nerve palsy, which recovered by 6 weeks. Nail impingement was seen in 1 (4%), Shoulder stiffness in 1 (4%) and none of the patients got infected. Functional results were excellent in 21(84%), Moderate in 3(12%) and poor in 1(4%). Conclusion: Closed intramedullary nailing offers a safe & Reliable method of fixing humeral Shaft fractures, with early fracture consolidation & Higher union rates. It provides early rehabilitation &Reduces the hospital Stay.